The English republican tradition and eighteenth-century France : between the ancients and the moderns - Hammersley, Rachel, 1974- (Studies in early modern European history., 2010)
This text offers an account of the role played by 17th- and 18th-century English Republican ideas in 18th-century France. Challenging some of the dominant accounts of the Republican tradition, it revises conventional understandings of what Republicanism meant in both Britain and France during the 18th century.